2020
DOI: 10.1002/acr.24084
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Nonsurgical Interventions for Trapeziometacarpal (Thumb Base) Osteoarthritis: A Systematic Review

Abstract: Objective. To synthesize the literature on the efficacy of existing nonsurgical interventions for trapeziometacarpal (TM) osteoarthritis (TMO). Methods. A medical librarian conducted an electronic search in 16 databases. Two authors independently carried out study selection, data extraction, and risk-of-bias assessment. The Agency for Healthcare Research and Quality guidance was followed to integrate a valid body of evidence from the existing systematic reviews. Intervention effects were estimated based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 75 publications
0
11
0
2
Order By: Relevance
“…Many experimental results have shown that W. somnifera improved VAS score by improving pain response, antioxidant status and general wellbeing The present data represent that herbs like turmeric, chopchini extract (Bark) and ginger used in HFPM-01 formulation have its promising effect on GI related complications like nausea, hyperacidity, heartburn and constipation etc. [20] The absence of gastric disturbance and improved compliance and quality of life can contribute to the better prognosis of the results in chronic OA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many experimental results have shown that W. somnifera improved VAS score by improving pain response, antioxidant status and general wellbeing The present data represent that herbs like turmeric, chopchini extract (Bark) and ginger used in HFPM-01 formulation have its promising effect on GI related complications like nausea, hyperacidity, heartburn and constipation etc. [20] The absence of gastric disturbance and improved compliance and quality of life can contribute to the better prognosis of the results in chronic OA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in early stages of TMO or when inflammation is predominant corticos- teroids infiltration, in combination with splinting, can provide long-term pain relief [43]. It remains unclear whether the volume injected into the joint or specific anti-inflammatory effects are responsible for pain reduction, as some studies have revealed that saline injections can provide similar results [9,42].…”
Section: Physical Therapymentioning
confidence: 99%
“…Pain can vary from episodic to pain related to a specific activity, sometimes accompanied by a background ache [7,8]. Grasping and pinching is often limited [9]. As the thumb is needed for countless daily activities and represents approximately 40% of overall hand function, limitation of its function can be very disabling [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The natural history can result in less symptomatic or stable end‐stage disease (3) or progress to pain and functional limitations interfering with patients’ quality of life (4–6). A range of conservative interventions is available, such as splints and exercise, but evidence for their effectiveness is sparse and of poor quality (7–11).
Outcome measures and treatments tailored to the unique impact of first carpometacarpal (CMC1) joint osteoarthritis (OA) are likely to improve outcomes.
…”
Section: Introductionmentioning
confidence: 99%